135 Real-World Data of Microvascular Decompression in Trigeminal Neuralgia: Analysis of 26 Tertiary Care Centers of the European Continent. (April 2023) - Sommer, Björn; Shiban, Ehab; Schatlo, Bawarjan; Rohde, Veit; Thomé, Claudius; Brito Silva Barbosa, Marcos Daniel; Jödicke, Andreas; Gandía González, Maria Luisa; Blasco, Guillermo; Demetriades, Andreas K.; Sure, Ulrich; Vanaclocha, Vincente; et al.
Abstract : INTRODUCTION: Patients with classic trigeminal neuralgia (TN) usually receive first-line treatment with carbamazapine. The known effect of wearing-off is hold against the result of expert single-center series of microvascular decompression (MVD) as a successful treatment option. However, real-world data regarding MVD is lacking. METHODS: A multicenter retrospective data analysis was performed in 26 European hospitals. Inclusion criteria were a) age >18 to 85 years, b) patients with classical TN, c) patients who underwent microvascular decompression (MVD) and d) minimum follow-up of 12 months. Primary outcome is pain-freedom at last follow up. Secondary outcome parameters were duration of symptoms prior to MVD, neurovascular conflict in MRI, time to pain recurrence, complications, and a tailored questionnaire. RESULTS: 1140 patients from 26 European institutions were analysed. Of those, 591 (346 female, 245 male, age (mean±SD) 60.1 ± 13.4 years) fulfilled the inclusion criteria. Mean duration of symptoms prior to surgery was 73.3 ± 67.0 months (6.1 ± 5.6 years). 73.3% of patients had a visible neurovascular conflict in MRI. After a follow-up 49.9 ± 36.8 months, 68.7% of patients were pain free or had occasional pain (BNI score 1 and 2). There was no correlation between symptom duration and time to pain recurrence. Involvement of SCA (61%) was associated with a high probability of pain freedom (p<0.01). Complications occurred in 31.6% of all cases, with hypoesthesia of the facial nerve being the most common event. Three out of four patients (74%) were satisfied with the treatment, and 72% would choose MVD as the preferred treatment option again. CONCLUSIONS: Microvascular decompression for trigeminal neuralgia is an effective treatment modality with excellent pain control. Two-third of patients were satisfied with the treatment.